Fourth Consensus Guidelines for the Management of Postoperative Nausea and Vomiting. (August 2020) - Gan, Tong J.; Belani, Kumar G.; Bergese, Sergio; Chung, Frances; Diemunsch, Pierre; Habib, Ashraf S.; Jin, Zhaosheng; Kovac, Anthony L.; Meyer, Tricia A.; Urman, Richard D.; Apfel, Christian C.; Ayad, Sabry; et al.
Abstract : This consensus statement presents a comprehensive and evidence-based set of guidelines for the care of postoperative nausea and vomiting (PONV) in both adult and pediatric populations. The guidelines are established by an international panel of experts under the auspices of the American Society of Enhanced Recovery and Society for Ambulatory Anesthesia based on a comprehensive search and review of literature up to September 2019. The guidelines provide recommendation on identifying high-risk patients, managing baseline PONV risks, choices for prophylaxis, and rescue treatment of PONV as well as recommendations for the institutional implementation of a PONV protocol. In addition, the current guidelines focus on the evidence for newer drugs (eg, second-generation 5-hydroxytryptamine 3 [5-HT3 ] receptor antagonists, neurokinin 1 (NK1) receptor antagonists, and dopamine antagonists), discussion regarding the use of general multimodal PONV prophylaxis, and PONV management as part of enhanced recovery pathways. This set of guidelines have been endorsed by 23 professional societies and organizations from different disciplines (Appendix 1). What Other Guidelines Are Available on This Topic? Guidelines currently available include the 3 iterations of the consensus guideline we previously published, which was last updated 6 years ago1–3 ; a guideline published by American Society of Health System Pharmacists in 19994 ; a brief discussion on PONV management as part of a comprehensive postoperative care guidelines5 ; focused guidelines published by the Society of Obstetricians and Gynecologists of Canada, 6 the Association of Paediatric Anaesthetists of Great Britain & Ireland7 and the Association of Perianesthesia Nursing8 ; and several guidelines published in other languages.9–12 Why Was This Guideline Developed? The current guideline was developed to provide perioperative practitioners with a comprehensive and up-to-date, evidence-based guidance on the risk stratification, prevention, and treatment of PONV in both adults and children. The guideline also provides guidance on the management of PONV within enhanced recovery pathways. How Does This Guideline Differ From Existing Guidelines? The previous consensus guideline was published 6 years ago with a literature search updated to October 2011. Several guidelines, which have been published since, are either limited to a specific populations7 or do not address all aspects of PONV management.13 The current guideline was developed based on a systematic review of the literature published up through September 2019. This includes recent studies of newer pharmacological agents such as the second-generation 5-hydroxytryptamine 3 (5-HT3 ) receptor antagonists, a dopamine antagonist, neurokinin 1 (NK1) receptor antagonists as well as several novel combination therapies. In addition, it also contains an evidence-based discussion on the management of PONV in enhanced recovery pathways. We have also discussed the implementation of a general multimodal PONV prophylaxis in all at-risk surgical patients based on the consensus of the expert panel.